CONTRASTIVE ANALYSIS ON THE THEME/RHEME STRUCTURE ON HEADLINES OF THE JAKARTA POST AND MEDIA INDONESIA - Rini, Setia (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
This study is to investigate the contrastive structure of Theme/ Rheme analysis in identifying marked and unmarked Themes in English and Indonesian headlines. The study takes as its starting point the assumption that the different choices of Theme/ Rheme, their organization at the local and global structures and the pres-entation of Given/New information of the headlines presented in English and Indonesian. This study designs a Discourse Analysis. It analyzes Theme/Rheme in Indonesian and English clauses. The study seeks to ana-lyze and compare the different choices of Theme/Rheme in the thematic structures. These issues are investi-gated in a corpus of English and Indonesian headline about lieu of law on direct regional election. Most of the Theme used was marked themes. Keywords: Contrastive, Theme and Rheme, Headline.